Metal-oxide and oxide-metal interaction effects on thin film oxide. The Ti/TiO2 and TiO2/Ti cases. - Mendoza, Sandra Marina (2003)
Through Auger electron spectroscopy (AES) and factor analysis (FA), we have studied the effect of metal–metal and metal–oxide interface interactions on the Ti oxide film formation. The passivation of Ti thin film oxidation is a thermally dependent process. It is possible, in consequence, to induce a further oxidation by heating the system. However, the complete oxidation of the thin film cannot be achieved in any case (for films thicker than 2 monolayers (ML)), due to substrate–Ti interactions. On the other hand, for the inverse configuration, metal over oxide, the strong Ti reactivity broadens the interface promoting the appearance of Ti2O3.